2011
DOI: 10.3758/s13415-011-0048-8
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the impact of mindfulness meditation training on working memory: A mathematical modeling approach

Abstract: We investigated whether mindfulness training (MT) influences information processing in a working memory task with complex visual stimuli. Participants were tested before (T1) and after (T2) participation in an intensive one-month MT retreat, and their performance was compared with that of an age- and education-matched control group. Accuracy did not differ across groups at either time point. Response times were faster and significantly less variable in the MT versus the control group at T2. Since these results… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
52
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 86 publications
(58 citation statements)
references
References 43 publications
4
52
2
Order By: Relevance
“…In line with this prediction, several prior studies have demonstrated that MT can improve performance on measures of selective and sustained attention (e.g., Allen et al 2012;Jensen et al 2012;Jha et al 2007;MacLean et al 2010;Zanesco et al 2013), and WM (Chambers et al 2008;Jensen et al 2012;Mrazek et al 2013;Quach et al 2016;Van Vugt and Jha 2011;Zeidan et al 2010; but see Morrison et al 2014), and can reduce performance lapses associated with mind wandering Morrison et al 2014;Mrazek et al 2013).…”
mentioning
confidence: 70%
“…In line with this prediction, several prior studies have demonstrated that MT can improve performance on measures of selective and sustained attention (e.g., Allen et al 2012;Jensen et al 2012;Jha et al 2007;MacLean et al 2010;Zanesco et al 2013), and WM (Chambers et al 2008;Jensen et al 2012;Mrazek et al 2013;Quach et al 2016;Van Vugt and Jha 2011;Zeidan et al 2010; but see Morrison et al 2014), and can reduce performance lapses associated with mind wandering Morrison et al 2014;Mrazek et al 2013).…”
mentioning
confidence: 70%
“…MBCT has additionally been shown to augment suppression of currently-irrelevant mental sets (74) and promote both cognitive flexibility and overall cognitive functioning (75), benefits which correlate with a reduction in depressive symptomology. Studies examining other MBIs with healthy participants similarly indicated improvements in cognitive abilities such as working memory (7677), cognitive flexibility (7879) and inhibition (80), with very limited evidence regarding attentional improvements (see (73) for a review). Although the specific impact of these cognitive improvements is yet to be established, such cognitive faculties are important factors in facilitating the disengagement from negating thinking patterns associated with depression and may be vital in addressing the cognitive deficits associated with numerous clinical conditions.…”
Section: Mechanismsmentioning
confidence: 99%
“…Such executive or cognitive control functions enhanced by mindfulness have been associated to the notion of cognitive flexibility (Kim et al 2011;Miller and Cohen 2001;Moore and Malinowski 2009). Other studies found that mindfulness training enhances working memory processes, which plays a key role in higher cognitive functions (Mrazek et al 2013;Quach et al 2016;van Vugt and Jha 2011).…”
Section: Introductionmentioning
confidence: 96%